Guideline for the management of hip fractures 2020: Guideline by the Association of Anaesthetists. (2nd December 2020) - Griffiths, R.; Babu, S.; Dixon, P.; Freeman, N.; Hurford, D.; Kelleher, E.; Moppett, I.; Ray, D.; Sahota, O.; Shields, M.; White, S.
Summary: We convened a multidisciplinary Working Party on behalf of the Association of Anaesthetists to update the 2011 guidance on the peri‐operative management of people with hip fracture. Importantly, these guidelines describe the core aims and principles of peri‐operative management, recommending greater standardisation of anaesthetic practice as a component of multidisciplinary care. Although much of the 2011 guidance remains applicable to contemporary practice, new evidence and consensus inform the additional recommendations made in this document. Specific changes to the 2011 guidance relate to analgesia, medicolegal practice, risk assessment, bone cement implantation syndrome and regional review networks. Areas of controversy remain, and we discuss these in further detail, relating to the mode of anaesthesia, surgical delay, blood management and transfusion thresholds, echocardiography, anticoagulant and antiplatelet management and postoperative discharge destination. Finally, these guidelines provide links to supplemental online material that can be used at readers' institutions, key references and UK national guidance about the peri‐operative care of people with hip and periprosthetic fractures during the COVID‐19 pandemic.